Frontalne i całopostaciowe wizerunki Chrystusa na ikonach bizantyńskich i ruskich. Schemat ikonograficzny - Olga Cyrek (Polonia Sacra)
The article describes the icons, where Christ is presented in the whole form and in frontal pose. On icons: “The Transfiguration”, “Ascension”, “Descent in to the Abyss”, “Saviour in Majesty” comes in many forms. In the “Descent into hell” in addition to our first parents there are also angels, prophets, demons and Satan. Pantocrator is presented in the Majesty in the midst of the heavenly powers in a row and on the sides deesis accompanied by Mother of God and John the Baptist who intercede for the people.